Energetics of carbon and nitrogen impurities and their interactions with vacancy in vanadium - 华娟 刘悦林 李恒帅 赵明文 刘向东 (Chinese physics B, 2016)
We studied the energetic behaviors of interstitial and substitution carbon （C）/nitrogen （N） impurities as well as their interactions with the vacancy in vanadium by first-principles simulations. Both C and N impurities prefer the octahedral site （O-site）. N exhibits a lower formation energy than C. Due to the hybridization between vanadium-d and N/C-p, the N-p states are located at the energy from -6.00 eV to -5.00 eV, which is much deeper than that from -5.00 eV to -3.00 eV for the C-p states. Two impurities in bulk vanadium, C-C, C-N, and N-N can be paired up at the two neighboring O- sites along the （111） direction and the binding energies of the pairs are 0.227 eV, 0.162 eV, and 0.201 eV, respectively. Further, we find that both C and N do not prefer to stay at the vacancy center and its vicinity, but occupy the O-site off the vacancy in the interstitial lattice in vanadium. The possible physical mechanism is that C/N in the O-site tends to form a carbide/nitride-like structure with its neighboring vanadium atoms, leading to the formation of the strong C/N-vanadium bonding containing a covalent component.